Simple method for screening of α-thalassaemia 1 carriers - Tayapiwatana C. (2014)
α-Thalassaemia 1 genetic disorder occurs when there is a deletion of two linked α-globin genes. The interaction between these abnormal genes leads to the most severe type of thalassaemia disease, haemoglobin (Hb) Bart's hydrops fetalis. The identification of α-thalassaemia 1 carriers and genetic counselling are essential for the prevention and control of severe thalassaemia diseases. In this study, we have developed a rapid screening method for identifying α-thalassaemia 1. A sandwich-type immunochromatographic (IC) strip test was developed, using the generated monoclonal anti-Hb Bart's antibody, to trace the Hb Bart's in haemolysates. When assayed by our IC strip test, all α-thalassaemia 1, HbH disease, HbH-Constant Spring (H-CS) disease, HbH-CS and heterozygous HbE (CSEA) Bart's disease, and homozygous α-thalassaemia 2 showed positive results. No false negative results were observed in these blood samples. In α-thalassaemia 2 heterozygotes, 83% of them showed positive reactivity. Among HbE (both homozygotes and heterozygotes), β-thalassaemia (heterozygotes, homozygotes and β-thalassaemia/HbE) and normal subjects, the IC strip test revealed negative reactivity of 100, 85 and 97%, respectively. These results indicate that this novel immunodiagnostic kit, in combination with red blood cell indices, is suitable for screening and ruling out mass populations for the presence of α-thalassaemia 1. © 2009 The Japanese Society of Hematology.